The Coral Reefs Health Level in The Local Use Zone of Lentea Island Wakatobi National Park, Indonesia - Hasan Eldin Adimu; Tezza Fauzan; Latifa Fekri; La Ode Abdul Fajar Hasidu; Ilham Antariksa Tsabaramo (Coastal and Marine Journal, 2023)
Coral reefs are marine resources that are most vulnerable to disturbances from both human and natural activities. Fishing activities that are not environmentally friendly such as bombardment and potassium are still found in coastal areas and threaten the resources in the conservation area. This research will look at the health condition of coral reefs in conservation areas, especially in local utilization zones. In this zone the activity of exploiting marine resources is very high, therefore data is needed to find out and prove whether the use of marine resources is damaging. Locations were selected at four stations on Lentea Island which are included in the local use zone in the conservation area. The assessment uses the PIT (Point Intercept Transect) method. The results of the assessment showed that the coral reefs on Lentea Island were in the bad to good category (24.0% -50.3%). This data shows that there are still destructive marine resource utilization activities in the local utilization zone.